S.A.F.M.A. CONCERT, 6th APRIL, 1967 (International Library of African Music, 1968)
On the 6th April, 1967, SAFMA (The South African Folk Music Association), held a concert at the Selborne Hall, Johannesburg, in aid of the Library and recognition of Dr. Tracey’s work.
Keywords: African Music